An Internet Tool for Creation of Cancer Survivorship Care Plans for Survivors and Health Care Providers: Design, Implementation, Use and User Satisfaction - Hill-Kayser, Christine E; Vachani, Carolyn; Hampshire, Margaret K; Jacobs, Linda A; Metz, James M (JMIR Publications, 2009)
BackgroundSurvivorship care plans have been recommended by the Institute of Medicine for all cancer survivors. We implemented an Internet-based tool for creation of individualized survivorship care plans. To our knowledge, this is the first tool of this type to be designed and made publicly accessible. Objective To investigate patterns of use and satisfaction with an Internet-based tool for creation of survivorship care plans. MethodsOncoLife, an Internet-based program for creation of survivorship care plans, was designed by a team of dedicated oncology nurses and physicians at the University of Pennsylvania. The program was designed to provide individualized, comprehensive health care recommendations to users responding to queries regarding demographics, diagnosis, and cancer treatments. After being piloted to test populations, OncoLife was made publicly accessible via Oncolink, a cancer information website based at the University of Pennsylvania which averages 3.9 million page views and over 385,000 unique visits per month. Data entered by anonymous public users was maintained and analyzed. Results From May 2007 to November 2008, 3343 individuals utilized this tool. Most (63%) identified themselves as survivors, but also health care providers (25%) and friends/family of survivors (12%). Median age at diagnosis was 48 years (18 - 100+), and median current age 51 (19 - 100+). Most users were Caucasian (87%), female (71%), and college-educated (82%). Breast cancer was the most common diagnosis (46%), followed by hematologic (12%), gastrointestinal (11%), gynecologic (9%), and genitourinary (8%). Of all users, 84% had undergone surgery, 80% chemotherapy, and 60% radiotherapy. Half of users (53%) reported receiving follow-up care from only an oncologist, 13% only a primary care provider (PCP), and 32% both; 12% reported having received survivorship information previously. Over 90% of users, both survivors and health care providers, reported satisfaction levels of "good" to "excellent" using this tool. ConclusionsBased on our experience with implementation of what is, to our knowledge, the first Web-based program for creation of survivorship care plans, survivors and health care providers appear both willing to use this type of tool and satisfied with the information provided. Most users have never before received survivorship information. Future iterations will focus on expanding accessibility and improving understanding of the needs of cancer survivors in the era of the Internet.